Peran Orang Tua dalam Memotivasi Belajar Shalat Anak di Era Globalisasi (Studi Kasus di Desa Untoro, Trimurjo Lampung Tengah) - Ariani, Findi; Ali, Muhammad; Asy'arie, Bima Fandi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
Seeing that the times have entered the era of globalization, this has become a problem with the condition of children in terms of worshiping and praying, which looks quite alarming; many of them are affected by technological advances. This study aims to determine (1) the practice of the five obligatory prayers. (2) to discover parents' role in motivating children to learn to pray. (3) to find out the inhibiting and supporting factors for the role of parents in motivating children to learn to pray in the era of globalization. The location of this research was carried out in Untoro Village, Trimurjo District. In this type of research, the author uses a variety of qualitative field research (field research). The results of this study are that (1) parents have become a good example for children; (2) Parents always teach the practice of prayer in various ways (3) Parents also guide in terms of prayer; (4) Parents always advise in terms of praying for children.